Relative age effect and its impact on athletic performance among Chinese elite youth male basketball players - Haitong Yu; Chengbo Yang (Scientific Reports)
Abstract This study aimed to explore the presence and magnitude of relative age effects (RAEs) among elite male Chinese youth basketball players. A total of 728 adolescent players and 60 teams in the 2023 Chinese Student (Youth) Games were included. Player efficiency rating (PER) was calculated to evaluate individual performance, and the relative age team achievement (RATA) score was used to assess team-related RAEs. Partial correlation analysis was conducted to explore the relationships between relative age and performance parameters, with height and weight as control variables. The results indicate a skewed distribution of birth dates in the U-16 group. In contrast, the U-18 group exhibited a more balanced distribution. In the U-16 competitions, relative age had significant positive correlations with points, assists and PER. However, in the U-18 competitions, a significant positive correlation was only observed for assists. At the team level, in both U-16 and U-18 competitions, there was no significant correlation between the relative age and team performance indicators such as average point differential, winning percentage, and team efficiency. Given that RAEs in youth basketball may lead to inequitable talent selection and developmental opportunities, this phenomenon warrants attention, and measures should be implemented to mitigate potential selection bias and talent loss.